Auxin Response Factor 2 (ARF2), ARF3, and ARF4 Mediate Both Lateral Root and Nitrogen Fixing Nodule Development in Medicago truncatula - Kirolinko, Cristina; Hobecker, Karen; Wen, Jiangqi; Mysore, Kirankumar S.; Niebel, Andreas; Blanco, Flavio Antonio; Zanetti, María Eugenia (Frontiers in Plant Science, 2021)
Auxin Response Factors (ARFs) constitute a large family of transcription factors that mediate auxin-regulated developmental programs in plants. ARF2, ARF3 and ARF4 are post-transcriptionally regulated by the microRNA390 (miR390)/Trans-Acting Small interference RNA 3 (TAS3) module through the action of TAS3 derived trans-acting small interfering RNAs (ta-siRNA). We have previously reported that constitutive activation of the miR390/TAS3 pathway promotes elongation of lateral roots but impairs nodule organogenesis and infection by rhizobia during the nitrogen-fixing symbiosis established between Medicago truncatula and its partner Sinorhizobium meliloti. However, the involvement of the targets of the miR390/TAS3 pathway, i.e., MtARF2, MtARF3, MtARF4a and MtARF4b, in root development and establishment of the nitrogen-fixing symbiosis remained unexplored. Here, promoter: reporter fusions showed that expression of both MtARF3 and MtARF4a was associated with lateral root development; however, only the MtARF4a promoter was active in developing nodules. In addition, up-regulation of MtARF2, MtARF3, MtARF4a/b in response to rhizobia depends on Nod Factor perception. We provide evidence that simultaneous knockdown of MtARF2, MtARF3, MtARF4a and MtARF4b or mutation in MtARF4a impaired nodule formation, and reduced initiation and progression of infection events. Silencing of MtARF2, MtARF3, MtARF4a and MtARF4b altered mRNA levels of the early nodulation gene Nodulation Signaling Pathway 2 (MtNSP2). In addition, roots with reduced levels of MtARF2, MtARF3, MtARF4a and MtARF4b, as well as arf4a mutant plants exhibited altered root architecture, causing a reduction in primary and lateral root length, but increasing lateral root density. Taken together, our results suggest that these ARF members are common key players of the morphogenetic programs that control root development and the formation of nitrogen-fixing nodules.